2010
DOI: 10.1159/000312716
|View full text |Cite
|
Sign up to set email alerts
|

Factors Responsible for Asthma and Rhinitis among Kuwaiti Schoolchildren

Abstract: Objective: The aim of this study was to assess the prevalence of asthma among schoolchildren and to determine the level house dust mites in Kuwaiti homes and its role in asthma and rhinitis. Subjects and Method: The International Study of Asthma and Allergy in Children questionnaire was distributed to schoolchildren in the age group of 5–7 years, after random sampling from all the five governorates of Kuwait. The questionnaires were completed and initiated by parents with the help of the investigator and paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This is surprising given the high frequency of asthma in the general pediatric population [17,18]. On the other hand, almost 30% of patients in the study had at least 1 episode of ACS, but it tended to be mild and had no influence on PFTs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is surprising given the high frequency of asthma in the general pediatric population [17,18]. On the other hand, almost 30% of patients in the study had at least 1 episode of ACS, but it tended to be mild and had no influence on PFTs.…”
Section: Discussionmentioning
confidence: 90%
“…However, other genetic and environmental factors associated with pulmonary function were not investigated. The reported prevalence rates of wheeze ever, current wheeze, and physician-diagnosed asthma among otherwise normal 13- and 14-year-old Kuwaiti schoolchildren were 13.4, 7.6, and 15.6%, respectively [17,18]. However, there are no reports among younger children or patients with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies (Abal et al 2010;Al-Dawood 2000) reported that many countries in MEA that were impacted by desert dust storms such as Kuwait and Saudi Arabia have a higher prevalence of asthma, particularly in the paediatric population, compared with European countries. Further, a total of 8,157 and 1,131 morbidity and mortality cases were attributed to high PM 10 and PM 2.5 concentrations, respectively, during dust events in Ahvaz (Iran), indicating once more the importance of dust events and their adverse health impacts .…”
Section: Health Assessmentmentioning
confidence: 99%
“…Studies related to dust and health issues were carried out recently by Abdal et al (2010) and Thalib and Al-Taiar (2012). It was found from these studies that dust storms have some impacts on respiratory and asthma admissions in hospitals in Kuwait.…”
Section: Introductionmentioning
confidence: 99%